1981
DOI: 10.1038/ki.1981.22
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction in the male patient with uremia: A reappraisal

Abstract: Partial or complete impotence is common in uremia. It is not clear whether the impotence is organic or psychogenic in nature and whether uremia itself or the state of chronic illness is responsible for it. We examined these questions, by psychiatric interviews and nocturnal penile tumescence (NPT), in 50 normal subjects, 48 patients with chronic uremia, including 23 patients treated with maintenance dialysis, and 22 patients with chronic illness and normal renal function. About 40 to 50% of patients with uremi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0
2

Year Published

1984
1984
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(57 citation statements)
references
References 19 publications
4
51
0
2
Order By: Relevance
“…1 In 1981 another study showed a prevalence of 50%. 5 Rodger, Fletcher, Devar and collaborators, while studying 100 chronic renal patients, found ED in 61% of the group. 6 A recent study of 68 patients undergoing peritoneal dialysis continued to show similar results; 63 had severe ED complaints.…”
Section: Discussionmentioning
confidence: 97%
“…1 In 1981 another study showed a prevalence of 50%. 5 Rodger, Fletcher, Devar and collaborators, while studying 100 chronic renal patients, found ED in 61% of the group. 6 A recent study of 68 patients undergoing peritoneal dialysis continued to show similar results; 63 had severe ED complaints.…”
Section: Discussionmentioning
confidence: 97%
“…Most of the studies in sexual dysfunctions in CRF patients have focused on impotence. Erectile dysfunction is common in patients with CRF and is observed in excess of 50% of these patients (Procci 1981). These data are based on results obtained from interviews with or by the completion of questionnaires by the patients and/or their spouses.…”
Section: Erectile Dysfunction In End Stage Renal Diseasementioning
confidence: 99%
“…Some relationship to depression was found (Harari et al, 1971;Abram et al, 1975;Sherman, 1975;Steele et al, 1976). A recent work by Procci et al (1981), however, shows no difference in regard to erectile difficulty or frequency of intercourse between depressed and nondepressed patients.…”
Section: Discussionmentioning
confidence: 97%